PENINGKATAN KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI MIND MAPPING PADA PEMBELAJARAN AKIDAH AKHLAK DI SMPS BABUSSALAM PEKANBARU - Muhammad Hafid; Risnawati; Granita (STKIP Subang, 2025)
Critical thinking skills were complex abilities that every student needed to possess in order to achieve success in their education. This study aimed to analyze the effectiveness of the mind mapping method in improving students' critical thinking skills in Akidah Akhlak learning among Grade VIII-3 students at Babussalam Islamic Junior High School Pekanbaru. The research employed a Classroom Action Research (CAR) approach with descriptive statistical analysis using percentage formulas. Data were collected through written tests, observation of student activities, and critical thinking skill assessments. The results of this study showed an improvement in students' critical thinking skills in cach cycle. This was indicated by the percentage obtained from the observation of student activities and test results given in each cycle. In the first cycle, the students' activity score was 61.36%, while in the second cycle it increased to 85.22% (categorized as very effective). In addition, teacher activity also increased from 67.14% in the first cycle to 81.90% in the second cycle (also categorized as very effective). The findings of this study indicated that the mind mapping method could improve students' critical thinking skills in Akidah Akhlak learning, and thus could be considered an alternative approach to enhance the quality of learning.